Status of fish diversity and fishing gears in the fishery of Nanthikadal Lagoon, Mullaitivu, Sri Lanka - Surenthar, P.; Sivashanthini, K. (University of Jaffna, 2022)
The Northern coast of Sri Lanka is home to a larger number of lagoons, totalling up to 804 km2. Nanthikadal lagoon is a significant lagoon that exists in the coastal zone of the Mullaitivu District between 9° 17’ N and 80° 48’E. Species occurrences and their types are good indicators to express the health status of the lagoon ecosystem. The present investigation was carried out for the first time to record the finfish and shellfish diversity, diversity indices and the fishing gears used to capture these fishes in the Nanthikadal lagoon by collecting monthly samples from the fish landing centres from September 2017 to August 2019. Collected species were identified using FAO species identification field guide. During the field survey, the number of organisms caught from all species were also counted. Diversity indices such as Dominance, Simpson, Shannon and Evenness were calculated by using PAST software. Fish numbers were graphically compared through cluster analysis by Unweighted Pair Group Method with Arithmetic mean (UPGMA). Fishing gears used and details on mesh size of nets were collected by using questionnaire and face to face interview with the fishermen. Seventeen finfish and five shellfish species belonging to seventeen families were identified during the study period. Tilapia mossambica made the highest percentage contribution (29.34%). The minimum contribution was reported by species such as Portunus pelagicus, Scylla serrata, Scatophagus argus, Lutjanus johnii, Tricanthus biaculeatus and Chanos chanos (<1%). The highest and lowest abundance was found in post-monsoon and pre-monsoon periods respectively. Simpson index and Shannon index were high in the monsoon season. Strongylura strongylura and Gerres abbreviates showed a close relationship based on month-wise cluster analysis. Cast net was the most commonly used, and legal fishing gear. Part-time fishermen actively participated in shrimp capturing from brackish water. In the present study, the important components of the lagoon fishery such as fish and usage of fishing gears were analyzed to determine the present status of Nanthikadal lagoon fishery. These findings will be helpful for stakeholders in this region for sustainable fishery management and ultimately supporting the Ministry of Fisheries and Aquatic Resource Development by providing required fundamental information to develop a lagoon management plan in the future.
Keywords: Nanthikadal lagoon; Diversity indices; Finfish; Shellfish